Digitization of the health sector in Pakistan: challenges and opportunities to online health communication: A case study of MARHAM social and mobile media. (July 2018) - Ittefaq, Muhammad; Iqbal, Azhar
Objective: Social and mobile media are playing a significant role in the digitization of health sectors globally. New technology provides an opportunity for stakeholders (i.e., patients and healthcare professionals) to engage with each other in virtual environments to discuss health-related issues. This study examines the role of social and mobile media in digitizing the health sector in Pakistan through MARHAM, the platform which is the subject of this case study. Method: A thematic content analysis of MARHAM's social media (Facebook group, Facebook page, and Twitter account) and mobile media application ("app" and website) were chosen for sampling. Some 6083 group posts, 1724 tweets and 1123 Facebook posts populated our sample. Results: Analysis results indicate that MARHAM's Facebook group most often fields patient inquiries. The most discussed health issues were: women's health issues (43.23%), children's diseases (16.63%), psychological issues (15.45%), dental issues (9.50%), skin problems (5.93%), others (5.04%), and obesity (4.19%). MARHAM's Facebook page and Twitter account were mainly used for health education and awareness. Their mobile application and website were used by healthcare professionals and for patient registration. Conclusion: The study's results suggest that MARHAM is playing a significant role in the health sector of Pakistan, addressing primarily women and children's issues through their Facebook group. Like many who have an online presence, MARHAM faces certain challenges, including the public's low literacy rates and scant Internet access.